2014
DOI: 10.1259/dmfr.20130237
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CT perfusion imaging for parotid neoplasms

Abstract: Objectives: To assess the value of CT perfusion imaging in the differentiation of different histological categorization of benign tumours from malignant tumours in patients with parotid neoplasms. Methods: CT perfusion was successfully performed in 62 patients with parotid neoplasms whose diagnoses were confirmed by surgery or biopsy. The software generated a tissue time-density curve (TDC) and measured blood volume, blood flow, mean transit time and capillary permeability surface product. One-way ANOVA and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 21 publications
3
37
1
Order By: Relevance
“…When compared with dualphased enhanced CT, we assumed that Type I TDC was similar to early increase and fast decrease, and type III TDC were similar to delayed enhancement. The TDC findings features for WTs and PAs in this study strongly supported the previous opinions [9][10][11][12][13]15] , but some differences were also depicted. Type II TDC for 2 WTs cases observed in present work, showed fast enhancement and gradual washout, which was similar to type C TDC described by Y Dong et al [10] .…”
Section: Pei (Hu)supporting
confidence: 91%
See 4 more Smart Citations
“…When compared with dualphased enhanced CT, we assumed that Type I TDC was similar to early increase and fast decrease, and type III TDC were similar to delayed enhancement. The TDC findings features for WTs and PAs in this study strongly supported the previous opinions [9][10][11][12][13]15] , but some differences were also depicted. Type II TDC for 2 WTs cases observed in present work, showed fast enhancement and gradual washout, which was similar to type C TDC described by Y Dong et al [10] .…”
Section: Pei (Hu)supporting
confidence: 91%
“…In additional, previous study had revealed false teeth could affect the CTP results [10] . In this study, 2 cases with false teeth resulting in low quantify TDC, were also excluded.…”
Section: Pei (Hu)mentioning
confidence: 95%
See 3 more Smart Citations